Higher Price, Lower Costs? Minimum Prices in the EU Emissions Trading Scheme - Jan Abrell; Sebastian Rausch; Hidemichi Yonezawa (ETH Zurich, CER-ETH - Center of Economic Research, 2017)
This paper examines the efficiency and distributional impacts of introducing a price floor in an emissions trading system (ETS) when environmental regulation is partitioned. We theoretically characterize the conditions under which a price floor enhances welfare. Using a multi-country multi-sector numerical general equilibrium model of the European carbon market, we find that moderate minimum price levels in the EU ETS can reduce the costs of EU climate policy by up to thirty percent and yield outcomes close to uniform carbon pricing. Moreover, most of the EU Member States would gain. Our results are robust with respect to parametric uncertainty in production and consumption technologies.
Keywords: H23; Q52; Q58; C68; 330; Emissions Trading; Price Floors; EU ETS; Partitioned Environmental Regulation; General Equilibrium; EU-Emissionshandel; Preisregulierung; Wirkungsanalyse; Verteilungswirkung; EU-Klimapolitik; Kosten; Allgemeines Gleichgewicht; EU-Staaten